2011
DOI: 10.1007/bf03404172
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Alcohol Spectrum Disorder Prevalence Estimates in Correctional Systems: A Systematic Literature Review

Abstract: Objectives: The objective of this study was to conduct a systematic search of the literature for studies that estimated the prevalence/incidence of Fetal Alcohol Spectrum Disorder (FASD) in correctional systems in different countries and, based on these data, to estimate a) the number of people with Fetal Alcohol Syndrome (FAS)/FASD within the criminal justice system population, and b) the relative risk of becoming imprisoned for individuals with FAS/FASD compared with those without FAS/FASD. Method:A systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
94
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(97 citation statements)
references
References 19 publications
2
94
0
1
Order By: Relevance
“…Such 'early' possible identification can then result in proper diagnosis by a clinician (as well as the specific impairments in the defendant) and highlight their need for appropriate and timely interventions which are specifically designed for individuals with FASD (Brown et al, 2019). The "criminal justice system is an ideal arena for intervention efforts aimed at the rehabilitation and prevention or reduction of recidivism in this unique population" (Popova et al, 2011). The case of Pora, discussed by Freckelton in detail in his paper, clearly highlights the need for criminal justice professionals (e.g., police, forensic mental health assessors, defence lawyers, prosecution lawyers and 9 judicial officers) to be aware of and alert to the potential impact that FASD may have on the defendants responses to questions asked of them during interrogation (Freckelton, 2016a).…”
Section: Urgent Need For More Research and For The Training Of Mentalmentioning
confidence: 99%
See 1 more Smart Citation
“…Such 'early' possible identification can then result in proper diagnosis by a clinician (as well as the specific impairments in the defendant) and highlight their need for appropriate and timely interventions which are specifically designed for individuals with FASD (Brown et al, 2019). The "criminal justice system is an ideal arena for intervention efforts aimed at the rehabilitation and prevention or reduction of recidivism in this unique population" (Popova et al, 2011). The case of Pora, discussed by Freckelton in detail in his paper, clearly highlights the need for criminal justice professionals (e.g., police, forensic mental health assessors, defence lawyers, prosecution lawyers and 9 judicial officers) to be aware of and alert to the potential impact that FASD may have on the defendants responses to questions asked of them during interrogation (Freckelton, 2016a).…”
Section: Urgent Need For More Research and For The Training Of Mentalmentioning
confidence: 99%
“…Another important finding which has emerged from active case ascertainment studies is that a significant proportion of individuals identified as having a FASD only became aware of this when they are in the criminal justice system. This is despite the fact that they had previously been diagnosed with other psychiatric mental health conditions (e.g., Popova, Lange, Bekmuradov, Mihic, & Rehm, 2011;Bower et al, 2018;Brintnell et al, 2019). In a systematic review on prevalence, Popova and colleagues estimated that youth with FASD are 19 times more likely to be incarcerated when compared to youth with no diagnosis of FASD (Popova et al, 2011).…”
mentioning
confidence: 99%
“…Thus, the criminal justice setting is likely to have a higher prevalence of individuals with FASD. A systematic review of studies carried out in the criminal justice system (eg, prisons) in 201118 found that all the studies had been carried out in either Canada (five studies) or the USA (one). Studies using active case ascertainment (two Canadian studies) found prevalences of FASD substantially higher than the general population at 10.8%–23.3%.…”
Section: Ascertaining Prevalencementioning
confidence: 99%
“…The prevalence of FASD in Canada is estimated to be between 2-3% and individuals impacted by FASD often face substantial burden [3]. Evidence suggests that this population experiences lower rates of academic achievement, higher rates of incarceration, increased risk of problematic substance use, and higher overall mortality than the general public [4][5][6][7]. In addition to significant impacts to patients' wellbeing, the annual economic burden of FASD to society is large and was estimated to be $1.9 billion in 2017 Canadian Dollars [8].…”
Section: Introductionmentioning
confidence: 99%